Foxp3+ regulatory T cells are expanded in severe atopic dermatitis patients. Issue 12 (26th August 2015) - Roesner, L. M.; Floess, S.; Witte, T.; Olek, S.; Huehn, J.; Werfel, T.
Abstract: Regulatory T cells (Tregs) are known to play critical roles in homeostasis and immune responses in the skin. Whether Treg frequencies are altered in atopic dermatitis (AD) patients has been addressed by several studies, leading to conflicting results. The detection of Tregs by FOXP3 expression may lead to false‐positive results as activated T cells without regulatory function may transiently upregulate this transcription factor. In contrast, measurement of the DNA methylation status of a region within the FOXP3 locus that is selectively demethylated only in bona fide Tregs (Treg‐specific demethylated region, TSDR) represents a reliable method to quantify Tregs. Here, we measured circulating Treg frequencies of adult patients and detected a positive correlation with disease severity. Subsequent surface marker analysis revealed higher frequencies of CD45RA + CCR7 ‐ tissue‐homing Tregs in the patient group with a tendency of reduced expression of CD39 compared with healthy donors, a marker for the highly suppressive TREM subtype.